Influência da temperatura e do pH do meio sobre a resistência à corrosão das ligas Al(20204-T3), Al(7010-T7) e Al(7050-T7) utilizadas na indústria aeronáutica - Balducci, Ivan [UNESP] (2002)
The influence of temperature and environment pH upon 2024-T3, 7010-T7 and 7050-T7 aluminum alloys corrosion in 5% (m/m) NaCI solution, aerated and deaerated, was investigated through electrochemical techniques (potentiodynamic tests, cyclic voltammetry and impedance). The measurements results allowed to determine two electrochemical behaviors in all the studied alloys: active dissolution at pH 3.0 and pitting corrosion at pH between 6.0 and 8.5. The aerated medium was more aggressive in this pH intervaL These differences of behavior were associated with the film conductivity, the covered area and the selective dissolution of substrates. When a film is present in aerated environment, the corrosion velocity is controlled by the diffusion of oxygen to the cathodic sites. In deaerated environment, the velocity is controlled by dissolution process of a protective film. In these studied conditions, the 2024-T3 was the most resistant to corrosion and the 7050-T7 alloy the least one. The corrosion mechanisms in aerated and deaerated environment (pH 6.0) do not change over a temperature range of 5°C to 50°C. In both environments, the increases of temperature lead to an increase of corrosion velocity. In deaerated environment, due to the presence of a protective film, the influence of temperature over corrosion velocity is less severe than in aerated solution. In both environments, the behavior of the 2024-T3 was more sensitive to temperature changes than the 7010-T7 and 7050-T7 alloys